Jewish childhood in Kraków : a microhistory of the Holocaust - Sliwa, Joanna (Rutgers University Press, 2021)
Winner of the 2020 Ernst Fraenkel Prize from the Wiener Holocaust Library​ Jewish Childhood in Kraków is the first book to tell the history of Kraków in the second World War through the lens of Jewish children's experiences. Here, children assume center stage as historical actors whose recollections and experiences deserve to be told, analyzed, and treated seriously. Sliwa scours archives to tell their story, gleaning evidence from the records of the German authorities, Polish neighbors, Jewish community and family, and the children themselves to explore the Holocaust in German-occupied Poland and in Kraków in particular. A microhistory of a place, a people, and daily life, this book plumbs the decisions and behaviors of ordinary people in extraordinary times. Offering a window onto human relations and ethnic tensions in times of rampant violence, Jewish Childhood in Kraków is an effort both to understand the past and to reflect on the position of young people during humanitarian crises.
Keywords: Jewish children -- Poland -- Kraków -- History -- 20th century.; World War, 1939-1945 -- Children -- Poland -- Kraków.; Children and war -- Poland -- Kraków -- History -- 20th century.; Holocaust, Jewish (1939-1945) -- Poland -- Kraków.; Jews -- Poland -- Kraków -- History -- 20th century.; Jewish ghettos -- Poland -- Kraków -- History -- 20th century.; Kraków (Poland) -- Ethnic relations -- 20th century.; Enfants juifs -- Pologne -- Cracovie -- Histoire -- 20e siècle.; Guerre mondiale, 1939-1945 -- Enfants -- Pologne -- Cracovie.; Enfants et guerre -- Pologne -- Cracovie -- Histoire -- 20e siècle.; Holocauste, 1939-1945 -- Pologne -- Cracovie.; Juifs -- Pologne -- Cracovie -- Histoire -- 20e siècle.; Ghettos -- Pologne -- Cracovie -- Histoire -- 20e siècle.; HISTORY -- General.; HISTORY / General; Children; Children and war; Ethnic relations; Jewish children; Jewish ghettos; Jews; Poland -- Kraków; 1900-1999; jew, jewish, judaism, antisemite, anti-semite, antisemitic, anti-semitic, holocaust, yiddish, cultural identity, identity, religion, ethnicity, zionist, zionism, israel, immigration, community, culture, jewish studies, wartime, German army, Germany, Jewish community, Poland, children, childhood, youth, Krakow, diaspora, child, concentration camp, survival, human rights, Childhood studies, humanitarian crisis, city life, adolescence, ghetto, jewish ghettos.; Electronic books.; History